2007
DOI: 10.1007/s10535-007-0048-2
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium-mediated transformation of Cry1C, Cry2A and Cry9C genes into Gossypium hirsutum and plant regeneration

Abstract: Three constructs harbouring novel Bacillus thuringiensis genes (Cry1C, Cry2A, Cry9C) and bar gene were transformed into four upland cotton cultivars, Ekangmian10, Emian22, Coker201 and YZ1 via Agrobacterium-mediated transformation. With the bar gene as a selectable marker, about 84.8 % of resistant calli have been confirmed positive by polymerase chain reaction (PCR) tests, and totally 50 transgenic plants were regenerated. The insertions were verified by means of Southern blotting. Bioassay showed 80 % of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…To generate plants that express the desired traits, different techniques for inserting genes into plants have been developed since the early 1980s ( De Block et al, 1984 ) and are currently widely used and commercially available ( James, 2014 ). Cotton transformation methods normally use co-cultures with A. tumefaciens ( Guo et al, 2007 ) and microprojectile bombardment ( Aragão et al, 2005 ). It is well known that the transformation efficacy is affected by the plant material, genotype/variety, and type of explant ( Wilkins et al, 2004 ; Rao et al, 2009 ; Anami et al, 2013 ; Chakravarthy et al, 2014 ; Juturu et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…To generate plants that express the desired traits, different techniques for inserting genes into plants have been developed since the early 1980s ( De Block et al, 1984 ) and are currently widely used and commercially available ( James, 2014 ). Cotton transformation methods normally use co-cultures with A. tumefaciens ( Guo et al, 2007 ) and microprojectile bombardment ( Aragão et al, 2005 ). It is well known that the transformation efficacy is affected by the plant material, genotype/variety, and type of explant ( Wilkins et al, 2004 ; Rao et al, 2009 ; Anami et al, 2013 ; Chakravarthy et al, 2014 ; Juturu et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In cotton plant, transgenic technology has been mainly used to induce the resistance against insect herbivores. Among the different transgenic approaches against insects, Cry gene encoding Bacillus thuringiensis toxin has gained a fabulous success against bollworms (Guo et al, 2007a;Rashid et al, 2008). Recently, tma-12 gene encoding insecticidal protein has been identified that gives substantial results against whitefly and cotton leaf curl viral disease (Shukla et al, 2016).…”
Section: Biotic Stressesmentioning
confidence: 99%
“…Hussain et al (2007) transformed a Pakistani cotton cultivar with snow drop Galanthus nivalis (GNA) and cry1Ac gene to encode resistance against sucking as well as chewing insect pests. Transgenic cotton lines expressing cry1C, cry2A and cry9C showed enhanced resistance against Heliothis armigera (Guo et al 2007). The efficacy of cry1F insecticidal protein was deemed satisfactory for the control of fall armyworm (Spodoptera frugiperda) in cotton by Siebert et al (2008) under field conditions.…”
Section: Insect-resistant Cottonmentioning
confidence: 99%